2019
DOI: 10.1016/s0140-6736(19)30195-3
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of minimally invasive surgery with thrombolysis in intracerebral haemorrhage evacuation (MISTIE III): a randomised, controlled, open-label, blinded endpoint phase 3 trial

Abstract: Enlighten-Research publications by members of the University of Glasgow http://eprints.gla.ac.uk Minimally invasive surgery with thrombolysis in intracerebral haemorrhage evacuation (MISTIE III): a randomised, controlled, open-label phase 3 trial with blinded endpoint

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
475
1
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 605 publications
(519 citation statements)
references
References 46 publications
11
475
1
6
Order By: Relevance
“…All patients were treated according to the guidelines of the German societies of Neurology and Neurosurgery. The indication for minimally invasive hematoma evacuation was based on previous findings [16,18,27,33] Further information on patient management and intraoperative imaging can be found in the online supplement. In addition to intraoperative imaging, a routine CT scan was performed on postoperative day (POD) 1.…”
Section: Patient Managementmentioning
confidence: 99%
“…All patients were treated according to the guidelines of the German societies of Neurology and Neurosurgery. The indication for minimally invasive hematoma evacuation was based on previous findings [16,18,27,33] Further information on patient management and intraoperative imaging can be found in the online supplement. In addition to intraoperative imaging, a routine CT scan was performed on postoperative day (POD) 1.…”
Section: Patient Managementmentioning
confidence: 99%
“…Coagulopathy and a sustained high systolic blood pressure (SBP) create an increased risk of ongoing bleeding, and are both associated with neurological deterioration (33). The risk of poor outcome following ICH is increased for all different anticoagulants in current use (28), although NOAC-treated ICH patients have smaller ICH volume, are less prone to haematoma expansion and have lower mortality than Warfarin-treated ICH patients (34)(35)(36)(37)(38)(39)(40). Approximately 25% of ICH patients are on antiplatelet therapy and their prognosis is worse than that of patients not on antiplatelet therapy (41).…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…MIS includes procedures such as stereotactic puncture and drainage, with or without administration of local clot fibrinolysis, endoscopy assisted surgery, and other techniques aiming to minimise surgical access trauma (156). The phase II trial (MISTIE II) of stereotactical application of a catheter within the ICH followed by local administration of rtPA showed positive effects on PHE formation and ICH residual volume and found the technique to be safe (157), however, the recently published phase III trial (MISTIE III) showed no positive effect on functional outcome (35).…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…12 This phenomenon of T2* non-hypointensity, related to early erythrolysis, demonstrated in the animal models, is being investigated in humans with MRI. 13 Currently, no definite intervention has been shown to be beneficial for ICH, be it hematoma evacuation 14,15 or iron chelation treatment such as deferoxamine. 16 However, there is significant enthusiasm as MISTIE III has shown that patients who have greater than 75% of their ICH evacuated are clinically significantly better than those managed conservatively.…”
mentioning
confidence: 99%